The Ontology of Actuality and Potentiality as a Way for a Speculative Approach to the Aporetics of Time - Lythgoe, Esteban (2024)
In this article we will show the process that allowed Ricoeur to apply the Aristotelian ontology of actuality and potentiality to his hermeneutics, and how this development ended up providing him with a speculative solution to the aporetics of time. We will distinguish two alternative solutions: the poetic solution, given in Time and Narrative and the speculative one, developed in Memory, History, Forgetting. Despite the importance of the existential analytic, we believe that the introduction of the Spinozian conatus was decisive for Ricoeur’s change of perspective.